Effect Size Digital Mathematics Textbook in Blended Learning Assisted by Schoology Improves Mathematical Problem Solving Ability for Polytechnic Students - I Ketut Darma; I Gede Made Karma; I Made Anom Santiana; Ni Wayan Sadiyani (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2023)
This study aims to determine the effect size of digital mathematics textbooks in blended learning assisted by Schoology to improve mathematical problem-solving abilities in polytechnic students. The research was conducted at the Bali State Polytechnic (PNB), using the Research & Development method with a 4-D model (define, design, develop, and disseminate). Currently, the dissemination stage is carried out through an effectiveness test using a quasi-experiment approach, with a one-group pretest-posttest design. The subjects are PNB engineering students in 2020/2021, and 10 classes are taken by purposive sampling. Data were collected using a mathematical problem-solving ability test and analyzed using a t-test, N-Gain scores, and effect size. The results of the analysis show that the effect size of digital mathematics textbooks to improve mathematical problem-solving skills in Schoology-assisted blended learning is very large. The implication is that increasing the ability to solve mathematical problems through blended learning assisted by Schoology for polytechnic students will be quite effective if it is facilitated by digital mathematics textbooks.